Price transmission from international to domestic markets - Friederike Greb; Nelissa Jamora; Carolin Mengel; Stephan von Cramon-Taubadel; Nadine Würriehausen (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2012)
This study aims to improve our understanding of the extent and speed of the transmission of international cereal prices to local markets in developing countries. We analyse two samples of price transmission (PT) estimates, one extracted from a comprehensive literature sample of 31 published papers and studies on cereal price transmission and one containing of own estimates of cereal PT using the FAO's GIEWS dataset. We also present the results of a non-parametric analysis of PT in which we analyse the share of periods in which domestic and international prices have jointly increased or decreased. We find a higher share of cointegrated commodity market pairs in the literature sample (79% compared to 43%). This may be due to publication bias. Cointegration is more prevalent for maize market pairs and less prevalent for rice market pairs. Both the literature and the GIEWS-based estimates point to average long-run PT coefficients of roughly 0.75 and average short-run adjustment parameters of roughly 0.09-0.11. In most cases domestic prices adjust to deviations from the long-run price relationship, but international prices do not. The only notable exception to this rule is rice, which suggests that the determination of international rice prices differs fundamentally from the determination of international wheat and maize prices. In a subsequent meta-regression analysis we measure how much of the variation in the samples of PT estimates can be explained by country- or product-specific factors. However, this analysis fails to generate compelling results. An analysis of domestic price volatility reveals that median volatility has increased since July 2007.
Keywords: C32; Q11; Q17; Q18; 330; price transmission; cointegration; developing countries; agricultural trade; maize; rice; wheat; commodity prices